RANCANGAN MODEL PENENTUAN UP AH MINIMUM KABUPATEN/PERKOTAAN (UMK/P) DI SUBOSUKAWONOSRATEN TAHUN 2006-2008 - Sutomo Sutomo; Yunastiti Purwaningsih (Muhammadiyah University Press, 2006)
This research aim is to compile design of calculation manual program of regency/city minimum wage (UMK) for worker paid attention various consideration, and agreed on by various relevant side in determination of minimum wage in Subosukawonosraten at period 2006-2008. This research is expected well for worker and for council of remunerating region as consideration material to all representatives of worker union and entrepreneur in determining proposal of regency and city minimum wage at period 2006-2008.This research regarding base making of design model to determine UMK/P. Data that needed is KHM and KHL collected with survey method to merchants in some market in Subosukawonosraten, another data are inflation, PDRB, and labors amount from data publication of BPS Subosukawonosraten. Model used is projection method to determine level of UMK, the projection appropriate with Kepmenaker number 1, 1999, Permenaker number 17, 2005, and modification of model projection.The result of this research is guide book of UMP/K determination which contain data, formula and its simulation, determination result of UMK for Subosukawonosraten region, and identify its supporting data.